Not all Americans are creationists. Not all creationists are American (Italian original version) - Marco Ferrari (JCOM: Journal of Science Communication, 2006)
In addition to their intrusive presence in American schools, creationists - or more modern epigones thereof, known as “intelligent designers” - are also and unexpectedly to be found in other countries. Take the United Kingdom as an example. Over the past few years, Darwin’s homeland has actually been witnessing attempts to introduce literal faith in the Bible into school programmes in a way which does not significantly differ from the one adopted in the United States. It is multi-billionaire Howard H. Ahmanson who generously finances the Discovery Institute across the Atlantic, one of the dissemination centres of the creationist “creed”.